Dynamic modeling of the effect of water management on polymer electrolyte fuel cells performance. (19th February 2020) - Culubret, S.; Rubio, M.A.; Sanchez, D.G.; Urquia, A.
Abstract: Water management in Polymer Electrolyte Fuel Cell (PEFC) is a key factor in fuel cell performance, and it is an important contributor to the proton exchange membrane durability. Water droplet accumulation in the channel causes non-uniform distribution of gas pressure and spatial inhomogeneity of the local current density in potentiostatic mode. These spatial and temporal fluctuations in the operating conditions imply unequal use of the membrane surface and the catalyst layer, producing uneven degradation and aging of the Membrane Electrode Assembly (MEA). In order to study the dynamic and spatial performance of the fuel cell, a three-level model has been developed. The model is composed of a two-phase, where steam and liquid water drops movement are considered in the channel model; liquid water and gas diffusion are considered in Gas Diffusion Layers (GDLs) model; and finally, the electrochemical reactions are represented in the electrochemical model. The complete model provides a wider understanding of the effect of water on PEFCs and allows to analyze the local current density and the water distribution in response to experimental set-up parameters such as anode and cathode gas flows, total current or channel geometries. The model has been validated using neutron images and segmented cells technique to evaluate the spatial distribution of liquid water and current density in the cell. The developed model and the simulation procedure proposed in this paper allow obtaining long-term dynamic simulations with low computational effort. Highlights: Model composed of submodels of channels, GDL, membrane and electrochemical reactions. Model validated with spatial distribution of water and current density experiments. Accurate model solver is capable to obtain simulations with a low computational cost.